Moral Observer-Licensing in Cyberspace - Yawei Ran; Yubo Hou; Zhiwen Dong; Qi Wang (Behavioral Sciences, 2022)
Moral observer-licensing happens when observers condone actors’ morally questionable conduct due to the actors’ history of moral behaviors. In four studies (N = 808), we investigated this phenomenon in the context of cyberspace and its contributing factors and boundary conditions. The pilot study determined what participants perceived as typically moral and immoral behaviors in cyberspace. Then, in Study 1, participants condemned a story character’s online immoral behavior less often when they were informed of the character’s prior online moral behavior than when they were not, which indicates moral observer-licensing in cyberspace. Study 2 confirmed the presence of moral observer-licensing in cyberspace and further demonstrated that a character’s prior moral or immoral behavior online respectively reduces or intensifies the perceived negativity of the character’s subsequent immoral behavior. Finally, Study 3 showed that participants who identified with the victim in a hypothetical scenario showed less forgiveness and more condemnation of a character’s immoral behavior than those who identified with the perpetrator or the bystander. These findings are of theoretical and practical significance for our understanding of cyber ethics.